2023
DOI: 10.1002/advs.202301341
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multifunctional Electronic Skins with Low‐Coupling for Complicated and Accurate Human–Robot Collaboration

Abstract: Multifunctional capability and low coupling electronic skin (e-skin) is of great significance in advanced robot systems interacting with the human body or the external environment directly. Herein, a multifunctional e-skin system via vertical integrated different sensing materials and structures is presented. The multifunctional e-skin has capacity sensing the proximity, pressure, temperature, and relative humidity simultaneously, with scope of 100-0 mm, 0-30 N, 20-120 °C and 20-70%, respectively. The sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The superhydrophilic surface has a high surface energy, which can strongly interact with micro- and nano water droplets. As a result, the water droplets can be rapidly captured when the fog passes through. On a superhydrophilic surface, a water droplet can fully spread with a static water contact angle (SWCA) close to 0° as depicted in Figure a. In 1997, Wang et al conducted pioneering research on the superhydrophilicity of titanium dioxide, which catalyzed further studies on the fabrication and application of superhydrophilic surfaces. Fish scales are composed of calcium phosphate, protein, and a thin layer of mucus.…”
Section: Superwettable Surfacementioning
confidence: 99%
“…The superhydrophilic surface has a high surface energy, which can strongly interact with micro- and nano water droplets. As a result, the water droplets can be rapidly captured when the fog passes through. On a superhydrophilic surface, a water droplet can fully spread with a static water contact angle (SWCA) close to 0° as depicted in Figure a. In 1997, Wang et al conducted pioneering research on the superhydrophilicity of titanium dioxide, which catalyzed further studies on the fabrication and application of superhydrophilic surfaces. Fish scales are composed of calcium phosphate, protein, and a thin layer of mucus.…”
Section: Superwettable Surfacementioning
confidence: 99%
“…For instance, Li et al proposed a multifunctional e-skin that used piezothermal transduction for contact-forces detection and capacitive transduction for proximity sensing [15]. Ge et al reported a multimodal e-skin system that vertically integrated different sensing materials and structures to sense proximity, pressure, temperature, and relative humidity simultaneously [16]. Hughes et al designed a robotic skin that used an array of optical sensors embedded in a layer of PDMS silicone; it could detect deformations in the PDMS caused by applied forces and the proximity of obstacles [17].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic skins (e-skins) are is rapidly developing to meet the needs of the above applications (Rybak et al, 2023;Gao et al, 2023). In terms of tactile sensing, e-skins are already able to detect signals such as proximity, pressure or tension, respectively (Ge et al, 2023;Li et al, 2022;Zhou et al, 2021). However, due to the mutual interference between detected signals, it is di cult for the device to distinguish between many different signals at the same time.…”
Section: Introductionmentioning
confidence: 99%